Confronting the past in a polarized present: The effect of Holocaust representations on mobilization for symbolic justice and against antisemitism - Berenike Firestone; Ruth Ditlmann; Oguzhan Turkoglu (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
Awareness of past atrocities is widely seen as critical for restoring justice and building resilient democracies. Yet, confronting people with past injustice committed by their group can also lead to defensiveness. Through a survey experiment (n=2,198), we measured the effect of three different prototypical forms of information about the Holocaust on intentions to commemorate the Holocaust, intentions to counter antisemitism, and attitudes towards minoritized groups. We find that all three forms demonstrate overall effectiveness in mobilizing individuals for commemoration and against antisemitism and improving their attitudes towards minoritized groups. We find heterogeneous treatment effects by party affiliation. For far-right supporters, reading about the story of an individual victim is particularly effective. For others, formats that center the sheer extent of atrocities or focus on symbolic justice efforts have greater mobilizing potential. We repeated the survey with the same respondents three months later (Nov 2023), following the start of the Israel-Gaza war, and found that means and treatment effects are overall stable despite the change in context. The results demonstrate the power of providing people with information about past atrocities and injustice for political mobilization and prejudice reduction.
Keywords: 320